International variation in caesarean section rates and maternal obesity. (July 2013) - O'Dwyer, V.; Layte, R.; O'Connor, C.; Farah, N.; Kennelly, M. M.; Turner, M. J.
<x xml:space="preserve">Abstract</x> This study examined variations in caesarean section (CS) rates associated with a woman's birthplace and differences in maternal adiposity. Women were enrolled in the 1st trimester. Maternal adiposity was assessed by body mass index (BMI) and bioelectrical impedance analysis (BIA). Irish women were compared with women born in the 14 countries who joined the European Union (EU) before 2004 (EU 14), and with those born in 12 countries who joined following enlargement (EU 12). Of the 2, 811 women enrolled, 2, 235 women were born in Ireland, 100 in EU 14 countries and 476 in EU 12 countries. Based on a BMI > 29.9 kg/m2, maternal obesity was higher in Irish (19.8%; n = 443) and EU 14 women (19.0%; n = 19) compared with EU 12 women (9.5%; n = 45), p < 0.001. BIA of maternal body composition confirmed increased adiposity in both the Irish and EU 14 women. Variations in emergency CS rates in primigravidas based on the woman's birthplace were associated with maternal adiposity and induction of labour, both modifiable risk factors for CS. We recommend, therefore, that induction of labour in obese primigravidas should be undertaken only in carefully considered clinical circumstances. Our findings also suggest economic development in Europe may drive an increase in the CS rates mediated through increased levels of maternal obesity and, therefore, public health interventions should focus on optimising a woman's prepregnancy weight.